Gender role identity, personality factors, and psychiatric symptoms among American adults: the Nathan Kline Institute Rockland Sample - Rossi, Mathias; Arcand, Maryse; Schmidt, Mike; Sandfort, Theodorus G. M.; Jean-Baptiste, Francelyne; Marin, Marie-France; Pantazatos, Spiro P.; Juster, Robert-Paul (Frontiers in Psychiatry, 2025)
IntroductionGender roles and personality traits have been reported to impact mental health. This study aims to investigate the relationship between gender role identity and psychiatric symptoms (anxiety, depressive symptoms, suicidality) as well as the moderating effects of personality traits in a community-representative sample of American adults.MethodsData from 741 participants (65.7% females) were analyzed from the Nathan-Kline Institute – Rockland Sample database, a community-ascertained lifespan cohort with participants undergoing multimodal brain imaging and comprehensive behavioral, cognitive, and psychiatric assessments. This analysis is restricted to adults and uses well-validated questionnaires to assess gender role identity, personality traits, symptoms of anxiety and depression, and suicidal thoughts/behaviors.ResultsResults revealed that having a gender role identity reversed to one’s birth-assigned sex (i.e., feminine gender role in males and masculine gender role in females) was associated with poorer mental health (i.e., more anxiety and depressive symptoms). This effect was stronger in males where femininity was positively associated with more suicidal thoughts and behaviors. Further analyses revealed that only low-extroverted feminine males reported higher anxiety, and only high-neurotic feminine males reported higher suicidality.ConclusionsThe present American study provides new understanding on gender role identity associations with mental health, while highlighting the importance of considering both birth-assigned sex and personality traits when studying gender role effects on psychiatric symptoms. We discuss the role of gendered traits and societal burden in relation to mental health.